Identification of the Avian RBP7 Gene as a New Adipose-Specific Gene and RBP7 Promoter-Driven GFP Expression in Adipose Tissue of Transgenic Quail - Ahn, Jinsoo; Shin, Sangsu; Suh, Yeunsu; Park, Ju Yeon; Hwang, Seongsoo; Lee, Kichoon (PLOS ONE, 2015)
The discovery of an increasing number of new adipose-specific genes has significantly contributed to our understanding of adipose tissue biology and the etiology of obesity and its related diseases. In the present study, comparison of gene expression profiles among various tissues was performed by analysis of chicken microarray data, leading to identification of RBP7 as a novel adipose-specific gene in chicken. Adipose-specific expression of RBP7 in the avian species was further confirmed at the protein and mRNA levels. Examination of the transcription factor binding sites within the chicken RBP7 promoter by Matinspector software revealed potential binding sites for adipogenic transcription factors. This led to the hypothesis that the RBP7 promoter can be utilized to overexpress a transgene in adipose tissue in order to further investigate the function of a transgene in adipose tissue. Several lines of transgenic quail containing a green fluorescent protein (GFP) gene under the control of the RBP7 promoter were generated using lentivirus-mediated gene transfer. The GFP expression in transgenic quail was specific to adipose tissue and increased after adipocyte differentiation. This expression pattern was consistent with endogenous RBP7 expression, suggesting the RBP7 promoter is sufficient to overexpress a gene of interest in adipose tissue at later developmental stages. These findings will lead to the establishment of a novel RBP7 promoter cassette which can be utilized for overexpressing genes of interest in adipose tissue in vivo to study the function of genes in adipose tissue development and lipid metabolism.